2005
DOI: 10.1248/bpb.28.1342
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Ca2+/Calmodulin-Dependent Protein Kinase II-Discovery, Progress in a Quarter of a Century, and Perspective: Implication for Learning and Memory

Abstract: Much has been learned about the activity-dependent synaptic modifications that are thought to underlie memory storage, but the mechanism by which these modifications are stored remains unclear. A good candidate for the storage mechanism is Ca 2؉ /calmodulin-dependent protein kinase II (CaM kinase II). CaM kinase II is one of the most prominent protein kinases, present in essentially every tissue but most concentrated in brain. Although it has been about a quarter of a century since the finding, CaM kinase II h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
125
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 134 publications
6
125
0
4
Order By: Relevance
“…The CAMK family regulates a range of processes associated with synaptic plasticity and cognition, including long-term potentiation (Fink and Meyer, 2002;Yamauchi, 2005), and has been associated previously with SCZ (Novak et al, 2006) and PCP treatment (Mouri et al, 2007b). We also found that subunits of the multifunctional calcium-dependent serine/ threonine phosphatase calcineurin A were altered in the PCP rats.…”
Section: Discussionsupporting
confidence: 61%
“…The CAMK family regulates a range of processes associated with synaptic plasticity and cognition, including long-term potentiation (Fink and Meyer, 2002;Yamauchi, 2005), and has been associated previously with SCZ (Novak et al, 2006) and PCP treatment (Mouri et al, 2007b). We also found that subunits of the multifunctional calcium-dependent serine/ threonine phosphatase calcineurin A were altered in the PCP rats.…”
Section: Discussionsupporting
confidence: 61%
“…1 B) and cortex (data not shown) within 2-3 weeks off-Dox and throughout the brain (data not shown) in all lines. Consistent with CaM kinase II␣ promoter activity (Ochiishi et al, 1994;Mansuy et al, 1998;Ochiishi et al, 1998;Yamauchi, 2005), the distribution and morphology of the Tag-positive cells indicated specific expression of TAg in neurons ( Fig. 1 B).…”
Section: Tag Expression In Postmitotic Neurons Activates the Cell Cycsupporting
confidence: 63%
“…Calcium dependent MAPK signalling has been suggested to play a role in glutamate receptor-mediated neuronal stress [133]. The influx of Ca 2+ into the cytosol from the extracellular space or from intracellular stores following stress stimuli may activate Ca 2+ /calmodulin kinases, which in turn can stimulate the activation of all three MAPK, especially JNK [190]. Alternatively, flavonoids may exert direct interactions with upstream signalling components required for the recruitment and activation of JNK in neurons.…”
Section: Stress-activated Protein Kinases: C-jun-n-terminal Kinase (Jmentioning
confidence: 99%